Peculiarities of mental status in patients with chronic obstructive pulmonary disease in different phases of the pathological process - Pertseva T.O.; Konopkina L.I.; Huba Iu.V. (Medičnì Perspektivi)
Chronic obstructive pulmonary disease (COPD) has a significant impact on various aspects of life of patients due to of daily symptoms, frequent exacerbations, comorbid conditions, including anxiety and depression. In the scientific literature there are different data on the relationship between the frequency of occurrence and severity of exacerbations of COPD on the one hand and concomitant depression and increased anxiety on the other hand. The aim of our study – to examine frequency and severity of depression and anxiety in patients with COPD exacerbation and in stable phase of the disease in patients with varying terms of remission. We examined 108 patients with COPD, which were divided into two groups. The main group – 16 patients with COPD were examined in two visits: in exacerbation and after two months of its completion. A comparison group – 92 patients with COPD in stable phase of the disease for at least three months. Examination of patients included general clinical methods, evaluation of clinical symptoms of COPD, evaluation of mental status using Hospital Anxiety and Depression Scale. It was found that symptoms of depression and anxiety are more expressied in patients with COPD exacerbation than in the stable phase. It was determined that the frequency of depression and anxiety in patients with COPD tends to decrease in two months after the exacerbation. It was also shown that mild depression and anxiety prevail in COPD patients with impaired mental state. In addition, there was found correlation between severity of dyspnea and depression severity in COPD patients with concomitant depression in the stable phase of the disease.